2002
DOI: 10.1091/mbc.01-06-0301
|View full text |Cite
|
Sign up to set email alerts
|

Sum1, a Component of the Fission Yeast eIF3 Translation Initiation Complex, Is Rapidly Relocalized During Environmental Stress and Interacts with Components of the 26S Proteasome

Abstract: Eukaryotic translation initiation factor 3 (eIF3) is a multisubunit complex that plays a central role in translation initiation. We show that fission yeast Sum1, which is structurally related to known eIF3 subunits in other species, is essential for translation initiation, whereas its overexpression results in reduced global translation. Sum1 is associated with the 40S ribosome and interacts stably with Int6, an eIF3 component, in vivo, suggesting that Sum1 is a component of the eIF3 complex. Sum1 is cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 74 publications
(87 reference statements)
3
45
0
Order By: Relevance
“…To date, we have been unable to visualize stress granules in Saccharomyces cereviseae under a variety of conditions (data not shown), although they can be detected in Saccharomyces pombe (Dunand-Sauthier et al 2002). However, several observations in mammalian cells suggest that P-bodies and stress granules are distinct structures.…”
Section: P-bodies May Function In Stress Responsesmentioning
confidence: 90%
“…To date, we have been unable to visualize stress granules in Saccharomyces cereviseae under a variety of conditions (data not shown), although they can be detected in Saccharomyces pombe (Dunand-Sauthier et al 2002). However, several observations in mammalian cells suggest that P-bodies and stress granules are distinct structures.…”
Section: P-bodies May Function In Stress Responsesmentioning
confidence: 90%
“…It has been proposed that the SGs serve as triage sites redirecting mRNA to either translation, storage or degradation . Interestingly, SG-like structures, containing eIF3, have been found in heat-shocked fission yeast Schizosacchomyces pombe (Dunand-Sauthier et al, 2002), but have not yet been reported in Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, bona fide SGs fitting all the above criteria were mainly reported in mammalian cells. However, several new studies have demonstrated the formation of SGs or SG-like bodies in Caenorhabditis elegans (Jud et al 2008), Trypanosoma brucei (Kramer et al 2008), Schizosaccharomyces pombe (Dunand-Sauthier et al 2002), and Saccharomyces cerevisiae (Buchan et al 2008;Groušl et al 2009), although SGs have yet to be documented in some other common model organisms such as Xenopus laevis, Danio rerio, and Drosophila melanogaster. The apparent evolutionary conservation of SGs as a stress survival mechanism underscores their importance throughout eukaryota.…”
Section: Introductionmentioning
confidence: 99%